Deciphering the genetic basis for vitamin E accumulation in leaves and grains of different barley accessions - Schuy, Christian; Groth, Jennifer; Ammon, Alexandra; Eydam, Julia; Baier, Steffen; Schweizer, Günther; Hanemann, Anja; Herz, Markus; Voll, Lars; Sonnewald, Uwe (Scientific Reports, 2019)
Tocopherols and tocotrienols, commonly referred to as vitamin E, are essential compounds in food and feed. Due to their lipophilic nature they protect biomembranes by preventing the propagation of lipid-peroxidation especially during oxidative stress. Since their synthesis is restricted to photosynthetic organisms, plant-derived products are the major source of natural vitamin E. In the present study the genetic basis for high vitamin E accumulation in leaves and grains of different barley (Hordeum vulgare L.) accessions was uncovered. A genome wide association study (GWAS) allowed the identification of two genes located on chromosome 7H, homogentisate phytyltransferase (HPT-7H) and homogentisate geranylgeranyltransferase (HGGT) that code for key enzymes controlling the accumulation of tocopherols in leaves and tocotrienols in grains, respectively. Transcript profiling showed a correlation between HPT-7H expression and vitamin E content in leaves. Allele sequencing allowed to decipher the allelic variation of HPT-7H and HGGT genes corresponding to high and low vitamin E contents in the respective tissues. Using the obtained sequence information molecular markers have been developed which can be used to assist smart breeding of high vitamin E barley varieties. This will facilitate the selection of genotypes more tolerant to oxidative stress and producing high-quality grains.
CRIS-Team Scopus Importer:2019-07-09

Manipulation of charge distribution in the arginine and glutamate clusters of the OmpG pore alters sugar specificity and ion selectivity - Schmitt, Christine; Bafna, Jayesh Arun; Schmid, Benedikt; Klingl, Stefan; Baier, Steffen; Hemmis, Birgit; Wagner, Richard; Winterhalter, Mathias; Voll, Lars (Biochimica Et Biophysica Acta-Biomembranes, 2019)
OmpG is a general diffusion pore in the E. coli outer membrane with a molecular architecture comprising a 14-stranded β-barrel scaffold and unique structural features. In contrast to other non-specific porins, OmpG lacks a central constriction zone and has an exceptionally wide pore diameter of about 13 Å. The equatorial plane of OmpG harbors an annulus of four alternating basic and acidic patches whose function is only poorly characterized. We have investigated the role of charge distribution for ion selectivity and sugar transport with the help of OmpG variants mutated in the annulus. Substituting the glutamate residues of the annulus for histidines or alanines led to a strong reduction in cation selectivity. Replacement of the glutamates in the annulus by histidine residues also disfavored the passage of pentoses and hexoses relative to disaccharides. Our results demonstrate that despite the wide pore diameter, an annulus only consisting of two opposing basic patches confers reduced cation and monosaccharide transport compared to OmpG wild type. Furthermore, randomization of charged residues in the annulus had the potential to abolish pH-dependency of sugar transport. Our results indicate that E15, E31, R92, R111 and R211 in the annulus form electrostatic interactions with R228, E229 and D232 in loop L6 that influence pH-dependency of sugar transport.
CRIS-Team Scopus Importer:2019-08-20
Keywords: E. coli; Ion selectivity; Liposome swelling assay; Porin engineering; Reversal potential; Sugar specificity